Education and Screening on Non-Communicable Diseases in Simokerto District, Surabaya, Indonesia - Minarti, Minarti; Luthfiyah, Sari; Nur Anugrahini, Hepta; Setyorini, Dhiana (Frontiers in Community Service and Empowerment, 2024)
Non-communicable diseases (NCDs) are one of the leading causes of death in the world. Indonesia is one of the countries facing the problem of both communicable diseases and non-communicable diseases (NCDs). Non-communicable diseases are usually asymptomatic and do not show certain clinical signs, so most people are not aware of the dangers of non-communicable diseases. Non-communicable diseases (NCDs) are one of the health problems in society that has increased every year, and is the largest contributor to the incidence of death in Indonesia. Non-communicable diseases can be triggered by a lack of physical activity, smoking, ineffective diet, stress, which can lead to increased pressure, increased blood sugar, and increased blood fat. The purpose of this community service is to increase community knowledge and carry out health screening on non-communicable diseases in residents in RT 01 and RT 02 RW 04 Tambakrejo Village, Simokerto District, Surabaya City. The method of the community service are lectures on hypertension and diabetes mellitus followed by discussion and questions and answers. Furthermore, a demonstration on health screening in non-communicable diseases was conducted. To determine the benefits of this activity, the participants' knowledge was tested using questions in the pre-test and post-test sessions. Assessment of the participants' knowledge by counting the correct answers to the questions on the test sheet.There is an 80% increase in knowledge of residents about the management of hypertension and diabetes mellitus. The results of the screening identification obtained data that the body mass index of the community is as follows 45.2% of people with obese conditions; 41% of residents have grade 1 hypertension with blood pressure between 140- 159/90-99 mmHg; the results of random blood sugar checks are normal (79%); uric acid checks on residents have normal results (82%); and cholesterol levels in the body range normal, namely 52 people (71%). It is important to support residents' activities in improving healthy living behaviour through joint exercises.. It is expected that the cadres will maintain the performance that has been achieved, and form working groups in their respective neighbourhoods to share the health information in improving the level of health..